Pretreatment HIV drug resistance predicts accumulation of new mutations in ART-naïve Ugandan children - Atmadja, Sandra Soeria; Amuge, Pauline; Nanzigu, Sarah; Bbuye, Dickson; Rubin, Johanna; Eriksen, Jaran; Kekitiinwa, Adeodata; Obua, Celestino; Gustafsson, Lars L.; Navér, Lars (Acta Paediatrica, 2020)
Aim: To assess the prevalence of pretreatment drug resistance (PDR) and its association with virologic outcomes after 24 weeks of antiretroviral therapy (ART), within an urban cohort of Ugandan children. Methods: Prospective observational study. Baseline and 24-week assessments of viral load (VL) and genotypic drug resistance to nucleoside reverse transcriptase inhibitors (NRTI) and non-nucleoside reverse transcriptase inhibitors (NNRTI) were performed. Results: Ninety-nine ART-naïve children (3-12 years) initiated efavirenz-based ART 2015- 2016 and 18/90 (20%) had baseline NRTI/NNRTI associated drug resistance mutations (DRMs). By 24 weeks, 72/93 (77%) children had VL < 40 copies/mL and a total of 23 children had DRMs. Children with PDR accumulated new DRMs with a mean number (SD) of 1.4 (2.35) new mutations compared to 0.26 (0.98) in 67 children with wild-type virus (P = .003). High pretreatment VL and PDR (number of baseline DRMs) predicted viremia (P = .003; P = .023) as well as acquired drug resistance (P = .02; P = .04). Conclusion: Pretreatment drug resistance to NNRTI/NRTI was common among ARTnaïve Ugandan children and predicted viremia and new resistance mutations after only especially when access to resistance testing and VL monitoring is poor. The long-term importance of PDR for non-NNRTI-based regimens needs further evaluation.
Keywords: Child; Drug resistance; Viral; Efavirenz; HIV; Uganda